SUKUK : TEORI DAN IMPLEMENTASI - Fasa, Muhammad Iqbal (Li Falah: Journal of Islamic Economics and Business, 2016)
Abstrak Sukuk is one of the most innovative products in the development of contemporary Islamic financial system. Sukuk growth of 84% per year when analyzed in the 2001 until 2007. Discussion of sukuk increasingly attracted the attention of academics and professional practitioners. Thus, the discussion paper will discuss in more depth theoretically about sukuk and implementation. The discussion on the definition of sukuk in etymology and terminology, history of the development of sukuk, Islamic legal basis of the sukuk, sukuk investment types, the development potential of sukuk in Indonesia, mechanism of profit sharing investment securities, as well as the difference between Sukuk and Bonds. Keywords: Investments, sukuk, bonds, and Islamic finance.